2018
DOI: 10.1021/acsmedchemlett.7b00364
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Herpes Simplex Virus-1 Entry into Human Cells by Nonsaccharide Glycosaminoglycan Mimetics

Abstract: Although heparan sulfate (HS) has been implicated in facilitating entry of enveloped viruses including herpes simplex virus (HSV), small molecules that effectively compete with this abundant, cell surface macromolecule remain unknown. We reasoned that entry of HSV-1 involving its glycoprotein D (gD) binding to HS could be competitively targeted through small, synthetic, nonsaccharide glycosaminoglycan mimetics (NSGMs). Screening a library of NSGMs identified a small, distinct group that bound gD with affinitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 46 publications
(130 reference statements)
0
34
0
Order By: Relevance
“…This is especially important because Our study is first to report a unique heparin mimetic, which has been previously been reported as a broad spectrum antimicrobial activity, as an inhibitor of HCMV. Earlier, we have demonstrated that SPGG inhibits HSV [50,51] and Chlamydia infection [66]. Since HSV and Chlamydia are known to exploit heparan sulfate during early stages of host pathogen interactions [66,67], SPGG's lowering of HCMV early gene expression is not too surprising considering that the viral entry is blocked in the first place.…”
Section: The Impact Of Spgg Treatment On Hcmv Spreadmentioning
confidence: 92%
See 4 more Smart Citations
“…This is especially important because Our study is first to report a unique heparin mimetic, which has been previously been reported as a broad spectrum antimicrobial activity, as an inhibitor of HCMV. Earlier, we have demonstrated that SPGG inhibits HSV [50,51] and Chlamydia infection [66]. Since HSV and Chlamydia are known to exploit heparan sulfate during early stages of host pathogen interactions [66,67], SPGG's lowering of HCMV early gene expression is not too surprising considering that the viral entry is blocked in the first place.…”
Section: The Impact Of Spgg Treatment On Hcmv Spreadmentioning
confidence: 92%
“…Another possibility is that SPGG mediates HCMV inhibition through multiple viral surface receptors, one of which is gB. The foundation for this expectation is that SPGG has been earlier shown to bind tightly to glycoprotein D of HSV [50,51]. Likewise, SPGG also inhibits Chlamydia infection through binding to its cell surface receptors [66].…”
Section: Spgg Inhibition Of Hcmv Entry Arises Partially From Binding mentioning
confidence: 99%
See 3 more Smart Citations